Perinatal outcomes and predictors of placental abruption: a retrospective study in an Ethiopian tertiary care center - Mesfin Tadese; Gebresenbet Getachew; Tirusew Nigussie Kebede; Toyba Ebrahim Yesuf; Saba Desta Tessema; Wogene Asefa Damesa; Gebeyehu Shumet Solomon (Frontiers in Public Health)
BackgroundPlacental abruption is a critical obstetric condition characterized by the premature separation of the placenta from the uterus, leading to severe maternal and fetal complications. In Ethiopia, the maternal and perinatal morbidity and mortality rates are alarmingly high, and placental abruption significantly contributes to these adverse outcomes. Despite its severity, there is a lack of comprehensive data on the burden, risk factors, and outcomes associated with placental abruption in the Ethiopian context. Thus, the study aimed to investigate the adverse perinatal outcomes of placental abruption and the factors associated with these outcomes among pregnant women admitted to the University of Gondar Comprehensive Specialized Hospital in Ethiopia.MethodAn institution-based retrospective cross-sectional study was conducted among 367 pregnant women who were admitted and managed for placental abruption from January 1, 2021, to January 1, 2023, at the University of Gondar Comprehensive Specialized Hospital. A simple random sample method was employed to choose the medical records. Data was collected using a checklist prepared with the KOBO collect tool and then exported to SPSS version 25.0. Variables having a p-value of less than 0.05 were deemed significant in the multivariable logistic regression analysis that was done. The adjusted odds ratio with a 95% confidence interval was reported.ResultThe prevalence of adverse perinatal outcome of placental abruption was 39.2, 95% CI: 34.3–44.1. The most common adverse outcomes were prematurity (25.6%), low birth weight (25.6%), and NICU admission (13.9%). Severe placental abruption [AOR (CI) = 8.82 (4.48–17.31)] and abruption at preterm gestation [AOR (CI) = 18.71 (9.59–36.42)] were significant predictors of adverse perinatal outcomes.ConclusionThe adverse perinatal outcomes of pregnancies complicated by placental abruption in this study were higher compared to other studies in Ethiopia. The degree of placental abruption and gestational age at diagnosis were significant associates of adverse perinatal outcomes. The study highlights the critical need for patient-centered counseling on antenatal bleeding to encourage early healthcare-seeking behavior, close follow up for those undergoing expectant management and the early detection and management of placental abruption to improve perinatal outcomes.